Guaranteeing development? the impact of financial guarantees - Winpenny, J. T. (Development Centre studies., 2005)
This volume tests the relevance and usefulness of guarantees to public and private actors in developing countries, especially for funding development projects. The presence of guarantees from multilateral or bilateral agencies can encourage financial flows either to increase, or to go where they otherwise might not. In this way, they can have a positive effect on sovereign ratings as well as their immediate direct effect on the local development environment. As a bonus, this study finds, development guarantees can help stimulate and stabilize local capital markets, thus providing future benefits for both public and private investors.--Publisher summary.